Association of Arch Forms in Class Ii Malocclusions - A Retrospective study - SOH, NURUL HUSNIYAH BINTI CHE; JAIN, RAVINDRA KUMAR; B, ARTHI (The journal of contemporary issues in business and government, 2021)
The vertical proportions of the face are significant in determining the esthetics and harmony of the face. Dental arch form is a reflection of underlying bone morphology, size and its shape. Correct identification of a patient's arch form is an important aspect to achieve a stable, functional and esthetic orthodontic treatment result. To evaluate the maxillary and mandibular dental arch forms in class II malocclusion. A retrospective cross-sectional study was conducted using the patient records from a dental hospital from June 2019 until March 2020. Patients diagnosed with class II malocclusion were selected and evaluated for its association with dental arch form. Data was collected and then subjected to statistical analysis. Statistical analysis: Microsoft Excel 2016 data spreadsheet was used to collect data and later exported to the SPSS software. Among 308 individuals diagnosed with class II malocclusion, ovoid arch form was the most frequent dental arch form found in both maxillary and mandibular arches. Broad and narrow arch forms showed nearly equal distributions in both arches among males and females. Within the limitation of our study, ovoid arch form seems to be the most prevalent arch form in Class II malocclusions subjects